Synthesis, structures and insulin-like activity of oxidovanadium(V) complexes with aroylhydrazones and ethylmaltol mixed-ligands. (5th September 2015) - Zhao, Xinlu; Chen, Xiangfei; Li, Jian; Chen, Jie; Sheng, Guihua; Niu, Fang; Qu, Dan; Huo, Yang; Zhu, Hailiang; You, Zhonglu
Graphical abstract: Three new oxidovanadium(V) complexes with aroylhydrazones and ethylmaltol mixed ligands were prepared and structurally characterized. The complexes can significantly decrease the blood glucose level in alloxan-diabetic mices. Abstract: Three new oxidovanadium(V) complexes with formula [VOLL′] (L = L 1 = N ′-(2-hydroxy-4-methoxybenzylidene)-4-hydroxybenzohydrazide for1, L = L 2 = N ′-(3-ethoxy-2-hydroxybenzylidene)pivalohydrazide for2, L = L 3 = 2-bromo- N ′-(3-ethoxy-2-hydroxybenzylidene)benzohydrazide for3, L′ = ethylmaltol), have been prepared. The complexes have been characterized by physico-chemical methods and single crystal X-ray determination. The V atom in each complex is coordinated by the NOO donor atoms of L, the OO donor atoms of L′, and one oxido group, forming octahedral coordination. The complexes were administered intragastrically to both normal and alloxan-diabetic mices for two weeks. The biological activity results show that the complexes at doses of 10.0 and 20.0 mg V·kg −1, can significantly decrease the blood glucose level in alloxan-diabetic mices, but the blood glucose level in the treated normal mices was not altered.